Effectiveness of behavioral vaccine on the oral health of children in Komarapalayam, South India: A randomized controlled pilot trial - N Umamaheswari; Sharath Asokan; S Thangakumaran (Wolters Kluwer Medknow Publications, 2017)
Background: Oral health education and promotion have emerged as a strong force against the traditional, dominant, and curative model of health practice. In pediatric dentistry, the utilization of an entertaining, easy to understand, and practical educational material is warranted. Behavioral vaccine is a simple, scientifically proven practice that is repeated to increase well-being. Aim: The aim of this study is to compare the effectiveness of conventional (instructional) dental hygiene program and "Good Behavior Game" (GBG) (contingency dental hygiene program - a behavioral vaccine) on the practice of oral hygiene among 5-7-year-old schoolchildren. Study Design: A total of sixty children aged 5-7 years were divided into two groups. Each group had thirty children. Materials and Methods: A pretest estimation of debris index-simplified (DI-S) was carried out. Children in Group A were given oral health education through instructional oral hygiene program. Children in Group B were allowed to participate in GBG daily for a week. The DI-S was recorded on the 8th day and 3 months after the intervention in both the groups. Results: In Group B, the good oral hygiene score dramatically increased from 10% to 93.3% 1 week after the intervention. There was a relative decrease in percentage of children who scored fair and poor also. At the end of 3-month follow-up, 90% of children had good oral hygiene. In Group A, there was a significant improvement in oral hygiene after 1 week, but it was not significant after 3 months. Conclusion: The present study was undertaken to advance the area of behavioral vaccine as an alternative for teaching basic oral health concepts in children. In this study, the GBG was found to be an effective intervention aid for educating children.